ICTs – Transforming Agricultural Extension? Report of the 6th Consultative Expert Meeting of CTA’s Observatory on ICTs - Richardson, Don (Technical Centre for Agricultural and Rural Cooperation, 2006)
No ICT project should commence before there is a commitment to achieving real development outcomes, and the links between those outcomes and the role for ICTs have been thoroughly assessed...